2019
DOI: 10.3389/fonc.2019.00798
|View full text |Cite
|
Sign up to set email alerts
|

Active-Scanned Protons and Carbon Ions in Cancer Treatment of Patients With Cardiac Implantable Electronic Devices: Experience of a Single Institution

Abstract: Background: Ionizing radiation was shown to be able to influence the function of cardiac implantable electronic devices (CIED's) leading to malfunctions with potentially severe consequences. Those effects presumably correlate with beam energy and neutron production. Thus, particle facilities are commonly cautious to treat patients with CIED's with particles, but substantial evidence is lacking. Methods and Materials: In total 31 patients were investigated, who have been treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 21 publications
(29 reference statements)
0
29
0
1
Order By: Relevance
“…It has been suggested that scanning particle beam therapy can reduce the secondary neutron volume dramatically [16,17,20,26]. Seidansaal et al have reported that there were no device malfunctions among 32 patients (10 PBT and 22 CIT) with CIED in their investigation [27]. Yonai et al have suggested that the neutron dose will be reduced with an order of magnitude with active scanning PBT and CIT [17,20].…”
Section: Discussionmentioning
confidence: 98%
“…It has been suggested that scanning particle beam therapy can reduce the secondary neutron volume dramatically [16,17,20,26]. Seidansaal et al have reported that there were no device malfunctions among 32 patients (10 PBT and 22 CIT) with CIED in their investigation [27]. Yonai et al have suggested that the neutron dose will be reduced with an order of magnitude with active scanning PBT and CIT [17,20].…”
Section: Discussionmentioning
confidence: 98%
“…The use of photon energies above 6 MV and the consequent neutron contamination are well studied risk factors for device malfunction 24,25 . Limited data are available on malfunctions during proton and carbon ion therapy 26,27 . In fact, the first use of proton therapy in a patient with ventricular tachycardia at the Centro Nazionale di Adroterapia Oncologica in Pavia/Italy was reported recently 28 .…”
Section: Discussionmentioning
confidence: 99%
“…promising as both have steeper dose gradients and, in the case of heavy ions, a higher biological effectiveness [5][6][7]. With this study we developed a protocol for definitive combined proton and carbon ion radiotherapy for patients with non-resectable osteosarcoma, whose systemic disease is targeted by standard chemotherapy such as that of the EURAMOS1 (European American Osteosarcoma Study) or the COSS96 (Cooperative Osteosarcoma Study group) protocols.…”
mentioning
confidence: 99%